PENILAIAN TINGKAT KESEHATAN BANK DAN PERUBAHAN HARGA SAHAM PT BANK RAKYAT INDONESIA AGRONIAGA TBK - Mubarok, Husni; Sari, Ratna Kurnia; Lesmana, Hendra; Suryanti, Ery (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2020)
Assessment of Bank Soundness Level and Changes in Share Price of PT Bank Rakyat Indonesia Agroniaga Tbk. A bank soundness assessment that stakeholders must know is critical, maximizing the intermediary institution's function to provide a paradigm in making investment decisions. In 2011, bank health was assessed using the RGEC component. The research years ranged from 2011 to 2019 through the public offering of PT Bank Rakyat Indonesia Agroniaga Tbk. shares on the Indonesia Stock Exchange. Researchers used a descriptive method with a quantitative case study design. This component is interesting for research to determine the effect of assessing RGEC component bank's soundness level on changes in stock prices scientifically. This indicator affects the independent variable Risk Profile, GCG, Earnings, Capital and has a positive and significant effect on the dependent variable on changes in share prices at PT BRI Agnoniaga Tbk. in 2011-2019.